Influence of Mg2+ substitution on structural, optical, magnetic, and antimicrobial properties of Mn–Zn ferrite nanoparticles - Abdel Maksoud, M. I. A.; El-Sayyad, Gharieb S.; Abokhadra, A.; Soliman, L. I.; El-Bahnasawy, H. H.; Ashour, A. H. (Journal of materials science. Materials in electronics, 2020)
Superparamagnetic nanoparticles (NPs) have a prominent interest from researchers in the field of industrial and biomedical applications. Herein, Mg 2+ -substituted Mn–Zn ferrites with nominal composition Mn 0.5 Zn 0 . 5− x Mg x Fe 2 O 4 NPs ( x = 0, 0.125, 0.25, 0.375, and 0.5) are synthesized via a facile sol–gel method. The samples after sintered at 1173 K are characterized via the X-ray diffraction technique (XRD), Fourier transform infrared (FTIR) spectroscopy, the energy-dispersive X-ray spectra (EDX), high-resolution scanning electron microscopy (SEM), ultraviolet - diffuse reflectance spectroscopy (UV-DRS), and vibrating sample magnetometer (VSM) technique. The XRD and FTIR patterns reveal that the formation of the cubic phase of Mn 0.5 Zn 0.5− x Mg x Fe 2 O 4 NPs. Also, small peaks associated with the phase of hematite (α-Fe 2 O 3 ) are observed due to the heating of spinel ferrites. The optical band gap for Mg 2+ -substituted Mn–Zn ferrites ranges between 1.36 and 1.78 eV. The saturation magnetization is enhanced with increasing Mg 2+ concentration. Furthermore, the M–H curves show a typical S-shaped exhibiting superparamagnetic nature for the studied samples. Also, the anisotropy constant enhances as Mg 2+ content increases in Mn–Zn NPs. Overall, the results revealed that the Mn 0.5 Zn 0.5− x Mg x Fe 2 O 4 NPs presented a unique properties, and consequently, they can be candidate materials for transformer's cores, antenna, and switching applications. On other hands, antimicrobial potential of the produced ferrite NPs was estimated towards multidrug-resistant (MDR) yeast and bacteria creating urinary tract infection (UTI). All the prepared ferrite NPs showed a hopeful antimicrobial potential upon all UTI-causing pathogens. Between them, Mn 0.5 Mg 0.5 Fe 2 O 4 NPs at 20 µg/ml was the most promising ferrite NPs produced superior antimicrobial activity due to the narrow band gap.